The larvae of Drusus franzressli Malicky 1974 and Drusus spelaeus (Ulmer 1920) (Trichoptera: Limnephilidae: Drusinae) with notes on ecology and zoogeography - Waringer, Johann; Graf, Wolfram; Bálint, Miklós; Kučinić, Mladen; Pauls, Steffen U.; Previšić, Ana; Keresztes, Lujza; Vitecek, Simon (Zootaxa, 2013)
Water quality monitoring is greatly dependent on identification tools for aquatic and semi-aquatic insects. Species-level identification improves resolution and precision of water quality assessment and requires comprehensive keys. With the aim of increasing the suitability of Drusinae for such applications, this paper gives a description of the hitherto unknown larvae of Drusus franzressli Malicky 1974 and Drusus spelaeus (Ulmer 1920). Information on the morphology of the lar-vae is given and the most important diagnostic features are illustrated. In the context of already available keys, the larvae of D. franzressli and D. spelaeus key together with Metanoea flavipennis (Pictet 1834), M. rhaetica Schmid 1956, D. im-provisus McLachlan 1884, D. nigrescens Meyer-Dür 1875 and Ecclisopteryx malickyi Moretti 1991. These species are easily separated by differences in larval morphology (dorsal outline and sculpturing of pronotum, presence/absence of lat-eral gills at 2nd and 3rd abdominal segments, start of lateral fringe) and their distribution ranges. Drusus franzressli is endemic to the Hellenic western Balkans whereas D. spelaeus is endemic to the western Alps (Grenoble area). In addition, ecological characteristics are briefly discussed.